Herakles: Lord and Guardian of the Fresh Waters - Segura, Eugenio Gómez (Ílu, 2023)
Heracles lacks a comprehensive program that includes many of his adventures. This pattern could originate from the fact that up to 21 of his enemies are descendants from seawater in all its mythological manifestations: Poseidon, Pontus, Phorcis, Cetos. This review can be compared to the cosmological role of Ninurta and Marduk in Mesopotamian mythology fighting to Tiamat and some of their acts and scenarios. We can therefore verify that Herakles does a great deal of their work: he controls mountains and freshwater springs, organizes river courses by opening gorges or building canals, cleans mouths and the seaside. Herakles would then be a good son of his father.